The influence of workload, role conflict and organizational climate on employee work stress at the department of transportation Sungai Penuh city - Wazirman Wazirman; Inriko Fardiansyah; Firdaus Firdaus; Adriyan Adriyan; Ardinal Ardinal (Journal of Educational and Learning Studies, 2021)
This study aims to see the effect of (1) Workload on employee work stress at the Department of Transportation of Sungai Penuh City. (2) Role conflict on employee work stress at the Department of Transportation of Sungai Penuh City. (3) Organizational climate on the work stress of employees at the Department of Transportation of Sungai Penuh City. (4) Workload, role conflict and organizational climate have a joint effect on employee work stress at the Sungai Penuh City Transportation Service.               The population in this study whole There are 33 employees at the Sungai Penuh City Transportation Service. The results of this study indicate that (1) Workloadprovide a positive influence on the work stress of employees at the Department of Transportation of Sungai Penuh City. (2)Role conflictprovide a positive influence on the work stress of employees at the Department of Transportation of Sungai Penuh City. (3)Organizational Climate give a negative influence on the work stress of employees at the Department of Transportation of Sungai Penuh City. (4)Workload, role conflict and organizational climate jointly have a significant effect on the work stress of employees at the Department of Transportation of Sungai Penuh City.